Evaluation of dry protonated calcium alginate beads for biosorption applications and studies of lead uptake - Lagoa, Ricardo (2017)
Alginate polysaccharide is a promising biosorbent for metal uptake. Dry protonated calcium alginate beads for biosorption applications were prepared, briefly characterized and tested for lead uptake. Several advantages of this biosorbent are reported and discussed in comparison with other alginate-based sorbents. The alginate beads contained 4.7 mmol/g of COOH groups, which suffered hydrolysis near pH 4. The Weber and Morris model, applied to kinetic results of lead uptake, showed that intraparticle diffusion was the rate-controlling step in lead sorption by dry alginate beads. Equilibrium experiments were performed and the data were fitted with different isotherm models. The Langmuir equation was the most adequate to model lead sorption. The maximum uptake capacity (qmax) was estimated as 339 mg/g and the Langmuir constant (b) as 0.84 l/mg. These values were compared with that of other sorbents found in the literature, indicating that dry protonated calcium alginate beads are among the best biosorbents for the treatment and recovery of heavy metals from aqueous streams.